Pengaruh Kepuasan terhadap Loyalitas Pelanggan Bengkel Resmi PT. Citra Thamrin Motor Kota Jambi - Nurhidayati, Nurhidayati (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The aim of this research is to obtain an overview of customer satisfaction and loyalty at the Official Workshop of PT. Citra Thamrin Motor Jambi City; and to analyze the influence of satisfaction on customer loyalty at the PT Official Workshop. Image of Thamrin Motor Jambi City. To answer the research objectives, the author used theoretical studies related to the research variables. The customer satisfaction variable used in this research refers to the theory put forward by Hawkin and Lonney in Tjiptono (2014:358), with indicators 1) Conformity to expectations; 2) Interest in visiting again; and 3) Willingness to recommend. Furthermore, the customer loyalty variable used in this research refers to the theory put forward by Ngo & Nguyen (2016), with indicators 1) Continuity; 2) Recommendations; and 3) Speak positively. Apart from that, the author also looked for relevant previous research in the form of previous articles/journals to support this research. This research uses quantitative descriptive methods. With a customer population of official PT. Citra Thamrin Motor in the second semester of 2023 has 1,224 customers. Meanwhile, the sample size in this study used the Slovin method with a margin of e = 10%, so that a sample of 93 was obtained. The analysis technique used the regression equation, continued by testing r Square and partial hypothesis testing with the t test. From the data processing carried out, the regression equation Y = 6.505 + 0.465.X + e is obtained. Meanwhile, from partial hypothesis testing, it has a sig value of <0.05, so it can be concluded that satisfaction has a partial positive and significant effect on customer loyalty. Based on the results of data analysis and discussion in this research, it can be concluded that partial customer satisfaction has a positive and significant effect on customer loyalty at the Official Workshop of PT. Image of Thamrin Motor Jambi City. Which means that the management of the Official Workshop of PT. Citra Thamrin Motor Jambi City can provide satisfaction to its customers, so this will also be followed by increasing customer loyalty.